Preoperative abdominal muscle elongation with botulinum toxin A for complex incisional ventral hernia repair. Issue 1 (5th August 2015) - Farooque, Faisal; Jacombs, Anita S. W.; Roussos, Emmanouel; Read, John W.; Dardano, Anthony N.; Edye, Michael; Ibrahim, Nabeel
Abstract: Background: Surgical repair of recurrent abdominal incisional hernia(s) can be challenging due to complex operative conditions, intense post‐operative pain, potential respiratory compromise and lateral muscle traction predisposing to early recurrence. We report our preliminary results with botulinum toxin A (BTA) injection causing flaccid paralysis (relaxation) of the lateral abdominal wall muscles prior to surgery. Methods: A prospective pilot study measured the effect of preoperative BTA prior to elective repair of recurrent abdominal hernias. Under ultrasound control, 2 weeks prior to surgery, 50 units of BTA was injected into the external oblique, internal oblique and transversus abdominis muscles at three sites on each side of the lateral abdominal wall (total dose 300 units). Pre‐ and post‐BTA abdominal computed tomography measured changes in abdominal wall muscle thickness and length. All hernias were repaired with laparoscopic or laparoscopic‐assisted mesh techniques in a single or two‐staged procedure. Results: Eight patients received BTA injections which were tolerated with no complications. Post‐BTA preoperative computed tomography showed a significant increase in mean length of lateral abdominal wall from 18.5 cm pre‐BTA to 21.3 cm post‐BTA ( P = 0.017) with a mean unstretched length gain of 2.8 cm per side (range 0.8–6.0 cm). All hernias were surgically reduced with mesh with no early recurrence. Conclusion: Preoperative BTA injection prior to complex abdominal hernia repair is a safe procedure that causes flaccid relaxation, elongation and thinning of the lateral abdominal muscles and decrease in hernia defect. Although further evaluation is required, BTA injections may be a useful adjunct to surgical repair of complex incisional hernias.